G274(P) Stabilisation, referral & transfer of acutely unwell children in myanmar. (12th March 2018) - Halbert, J; Malley, M; Monaghan, M; Roche, E; Babu, P; Oo, S; Bowyer, J; Wooton, M
Abstract : Aims: An Emergency Paediatric Care Programme in Myanmar provides training in the stabilisation and safe transfer of sick children. The transfer of seriously sick children may be necessary to ensure the appropriate level of care, but is fraught with difficulties. A review of current practice and local challenges was undertaken. Methods: In September 2015 a retrospective audit of children admitted with dengue to a Regional Centre was performed to identify reasons for referral. Local healthcare professionals were invited to complete a survey exploring barriers to referral pathways. Results: 34% of patients with dengue (n=269) were referred. Only 44% of referrals had a referral letter and 35% did not require tertiary care. Challenges identified included: Late presentation due to families' preference for traditional medicine, concerns about the quality of public healthcare, medical and transport costs Lack of referral guidelines, human resources and training Transfer of patients who had not first been stabilised Reluctance to acknowledge the potential benefits of transfers Deficiency in ambulances such that patients were transferred by public transport Solutions identified and implemented included: Development of referral guidelines and pathways Training in stabilisation and transfer Development of transfer checklists for emergency equipment and medications Identification of voluntary sector transport vehicles Identification of outpatient tertiary clinic appointments to reduce unnecessary acute referrals Conclusions: There is a deficiency in referral pathways between primary, secondary and tertiary healthcare facilities in Myanmar. Development of referral networks and the training of healthcare workers in the stabilisation and transfer of sick children is important to reduce morbidity and mortality.